Design and Fabrication of Centrifugal Microfluidic Chip Integrated with Screen-Printed Electrode for Electrochemical Biosensor Application - Do, Thi Ngoc Tram; Yoshiakia, Ukita; Truong, Thi Ngoc Lien (Old Journal, 2018)
In this work, the centrifugal microfluidic chip (CMF) was designed and fabrication to integrate onto transducer’s sensor in order to obtain minimization of reagent consumption used in sensor fabrication and to establish the automation process for bioelements immobilization. The results showed that the integrated centrifugal microfluidic chip (siphon type) with electrode can reduce 20 times of the chemical reagent consumption compared to dropping method in the sensor fabrication process. Furthermore, the integration of four chip simultaneously on the circular disk mounted on centrifugal system can improve the sensor fabrication efficiency. Experimental result of the fabricated sensor showed its high reproducibility (error lower than 5%) and the detection limit is 0.12 ng/mL which is appropriate for early diagnosis.